59. The Geology of the Iron King Mine - Paul Gilmour; Arthur R. Still (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1968)
The ore deposit of the Iron King mine occurs in a group of steeply-dipping metamorphosed eugeosynclinal volcanic and sedimentary rocks of Precambrian age. Within this sequence, the ore deposit lies at the contact of a unit made up of rhyolitic tuff and interbedded andesite and a structurally underlying series consisting of andesitic tuffs, minor rhyolitic tuffs, and argillaceous sediments. Field evidence suggests that these rocks have been overturned. The ore deposit is made up of a series of overlapping, conformable or bodies consisting of massive pyrite and associated lenses of massive quartz. These contain recoverable amounts of gold, silver, lead, zinc, and copper. A parallel zone of copper mineralization occurs within the hanging-wall rocks. The deposit is considered to belong to a large and important group characterized by mineralogical composition and the lithology and structural type of the host rocks. Evidence regarding the origin of the deposit is reviewed, and it is concluded that the ore bodies were formed through the agency of volcanic hot springs on, or near, a submarine surface of deposition